Low yields in avocados (Persea americana) : is poor pollination a contributing factor and can it be enhanced? - Du Toit, Elsie Sophia (University of Pretoria, 2021)
Dissertation (MSc(Agric) Horticultural Science)--University of Pretoria, 2021.